2016
DOI: 10.1021/acs.langmuir.5b03639
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Small Gold Nanoparticle Chains with High NIR Extinction through Bridging with Calcium Ions

Abstract: The self-assembly of citrate-capped Au nanoparticles (5 nm) resulted in branched nanochains by adding CaCl2 versus spherical nanoclusters for NaCl. These assemblies were formed between 1 s to 30 min by tuning the electrostatic repulsion and the interparticle bridging attraction between the cations and citrate ligands as a function of electrolyte concentration. For dilute Ca(2+), strong interparticle bridging favored particle attachment at chain ends. This resulted in the formation of small, branched chains wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 63 publications
(161 reference statements)
2
36
0
Order By: Relevance
“…Specifically, the CTAB layer is thought to be less well-organized on the surface of small spherical particles than it would be on the surface of a gold nanorod. Between the inherent organization of the capping agent on the metal core’s surface, and the possibility for capping agents to desorb from the particle surface under specific solution conditions 28 , Fg has several possible pathways to penetrate into the coating layer and interact with the metal surface. Previous studies have shown that citrate-coated gold NP’s are subject to aggregation in calcium-containing media (such as RPMI), which may be accompanied by ligand desorption.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the CTAB layer is thought to be less well-organized on the surface of small spherical particles than it would be on the surface of a gold nanorod. Between the inherent organization of the capping agent on the metal core’s surface, and the possibility for capping agents to desorb from the particle surface under specific solution conditions 28 , Fg has several possible pathways to penetrate into the coating layer and interact with the metal surface. Previous studies have shown that citrate-coated gold NP’s are subject to aggregation in calcium-containing media (such as RPMI), which may be accompanied by ligand desorption.…”
Section: Resultsmentioning
confidence: 99%
“…Conditions for forming linear, necklace-like [8,9] or globular [10] aggregates have been reported. The solvent used [4,11] passivating units, or the addition of salts [3,12] to influence the process leading, prevailingly, to one or the other aggregate morphology. Aggregation strongly affects the spectroscopic properties of AuNPs.…”
Section: Introductionmentioning
confidence: 99%
“…The wavelength of the resulting SPR can be tuned and varies with the morphology of the aggregate formed . Nanoparticle clusterization can be induced by addition of bifunctional crosslinking agents, surfactants and salts and it can substantially modify the properties of the nanoparticles for example, uptake rates by cells . Bisthiols are the most popular examples of crosslinking agents due to the high affinity of sulfur for gold .…”
Section: Introductionmentioning
confidence: 99%